О ГИДРОДИНАМИЧЕСКОЙ АКТИВНОСТИ ОБЕЗЗАРАЖИВАЮЩЕГО РЕАГЕНТА НА ОСНОВЕ ПОЛИГЕКСАМЕТИЛЕНГУАНИДИНА ГИДРОХЛОРИДА (World Science, 2019)
Proofs of the hypothesis about the possibility of use of Akvaton-10 reagent (PHMG-HCl) in technologies of drinking water treatment as an effective biocide and reagent for decreasing the hydrodynamic resistance of water is considered in this article. Results of the carried-out work allow to think of successful use in practice of Akvaton-10 reagent as for cleaning and disinfecting of drinking water, and as the highly effective agent reducing the hydrodynamic resistance of water for the solution of problems of energy saving and increase in overall performance of various hydraulic systems.